2017
DOI: 10.1007/jhep03(2017)089
|View full text |Cite
|
Sign up to set email alerts
|

Relative entropy and the RG flow

Abstract: We consider the relative entropy between vacuum states of two different theories: a conformal field theory (CFT), and the CFT perturbed by a relevant operator. By restricting both states to the null Cauchy surface in the causal domain of a sphere, we make the relative entropy equal to the difference of entanglement entropies. As a result, this difference has the positivity and monotonicity properties of relative entropy. From this it follows a simple alternative proof of the c-theorem in d = 2 space-time dimen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(105 citation statements)
references
References 36 publications
5
100
0
Order By: Relevance
“…If SSA is saturated for a certain choice of configuration, the density matrix is a quantum Markov state, implying again the structure for ρscriptAscriptC. One can moreover show that the density matrix does in fact factorize as described above by also invoking the saturation of α‐Renyi entropies (for arbitrary α) . In turn, this implies that the mutual information between scriptA and scriptC also vanishes; likewise boldI3false(scriptA:scriptB:scriptCfalse)=0.…”
Section: Discussionmentioning
confidence: 81%
“…If SSA is saturated for a certain choice of configuration, the density matrix is a quantum Markov state, implying again the structure for ρscriptAscriptC. One can moreover show that the density matrix does in fact factorize as described above by also invoking the saturation of α‐Renyi entropies (for arbitrary α) . In turn, this implies that the mutual information between scriptA and scriptC also vanishes; likewise boldI3false(scriptA:scriptB:scriptCfalse)=0.…”
Section: Discussionmentioning
confidence: 81%
“…(3.9) where we indicated that contributions from curvatures are suppressed by the short-distance cutoff [17]. In conformal perturbation theory around the UV fixed point we expect, on dimensional grounds,…”
Section: Modular Hamiltonian and Stress-tensormentioning
confidence: 94%
“…Unitarity and causality dictate that the EE depends on geometric properties of the boundary of the entangling region, and is the same for any Cauchy surface inside the causal diamond. As in [9,17], our strategy will be to deform the Cauchy surface towards the light-cone in order to equate the EE with the relative entropy. In more detail, let σ be the vacuum reduced density matrix for the UV fixed point theory…”
Section: Boundary Rg Flows and Entanglement Entropymentioning
confidence: 99%
See 1 more Smart Citation
“…For d = 2, 3 the proofs led to entropic cfunctions, which interpolate monotonically between the corresponding values at the fixed points, but are in general not stationary there [57][58][59], unlike Zamolodchikov's c-function. More recently, entropic reasoning based on tools that go beyond S has led to additional monotonicity statements and other restrictions on renormalization flows [60][61][62].…”
Section: Introductionmentioning
confidence: 99%